To find the solution, we need to check which value of f makes the inequality true when substituted into the equation.
1. f = -7:
2 * (-7) = -14. Since -14 is not greater than -16, f = -7 is not a solution.
2. f = -12:
2 * (-12) = -24. Since -24 is not greater than -16, f = -12 is not a solution.
3. f = -8:
2 * (-8) = -16. Since -16 is equal to -16, f = -8 is **not** a solution (the inequality requires greater than, not equal to).
4. f = -10:
2 * (-10) = -20. Since -20 is **greater than** -16, f = -10 is a solution.
Therefore, the only solution to the inequality 2f > -16 is f = -10.